Autonomic shift and increased susceptibility to infections after acute intracerebral hemorrhage - Sykora, Marek; Diedler, Jennifer; Poli, Sven; Rizos, Timolaos; Turcani, Peter; Veltkamp, Roland; Steiner, Thorsten (Stroke, 2011)
Background and Purpose— - - High infection rate after severe stroke may partly relate to brain-induced immunodepression syndrome. However, the underlying pathophysiology remains unclear. The aim of the current study was to investigate the role of autonomic shift in increased susceptibility to infection after acute intracerebral hemorrhage (ICH). - - Methods— - - We retrospectively analyzed 62 selected patients with acute ICH from our prospective database. Autonomic shift was assessed using the cross-correlational baroreflex sensitivity (BRS). The occurrence and cause of in-hospital infections were assessed based on the clinical and laboratory courses. Demographic and clinical data including initial stroke severity, hemorrhage volume, intraventricular blood extension, history of aspiration, and invasive procedures such as mechanical ventilation, surgical hematoma evacuation, external ventricular drainage, central venous and urinary catheters, and nasogastric feeding were recorded and included in the analysis. - - Results— - - We identified 36 (58%) patients with infection during the first 5 days of hospital stay. Patients with infections had significantly lower BRS, higher initial NIHSS scores, larger hemorrhages, and more frequently had intraventricular blood extension and underwent invasive procedures. In the multivariate regression model, decreased BRS (OR, 0.54; 95% CI, 0.32-0.91; P=0.02) and invasive procedures (OR, 2.32; 95% CI, 1.5-3.6; P<0.001) remained independent predictors for an infection after ICH. - - Conclusions— - - Decreased BRS was independently associated with infections after ICH. Autonomic shift may play an important role in increased susceptibility to infections after acute brain injury including ICH. The possible therapeutic relevance of autonomic modulation warrants further studies.